Ketogenic diet aggravates cardiac remodeling in adult spontaneously hypertensive rats - You, Yuehua; Guo, Yongzheng; Jia, Ping; Zhuang, Biaobiao; Cheng, Yu; Deng, Hongpei; Wang, Xiaowen; Zhang, Cheng; Luo, Suxin; Huang, Bi (Nutrition & metabolism, 2020)
Background Ketogenic diet (KD) has been proposed to be an effective lifestyle intervention in metabolic syndrome. However, the effects of KD on cardiac remodeling have not been investigated. Our aim was to investigate the effects and the underling mechanisms of KD on cardiac remodeling in spontaneously hypertensive rats (SHRs). Methods 10-week-old spontaneously hypertensive rats were subjected to normal diet or ketogenic diet for 4 weeks. Then, their blood pressure and cardiac remodeling were assessed. Cardiac fibroblasts were isolated from 1- to 3-day-old neonatal pups. The cells were then cultured with ketone body with or without TGF-β to investigate the mechanism in vitro . Results 4 weeks of KD feeding aggravated interstitial fibrosis and cardiac remodeling in SHRs. More interestingly, ketogenic diet feeding increased the activity of mammalian target of rapamyoin (mTOR) complex 2 pathway in the heart of SHRs. In addition, β-hydroxybutyrate strengthened the progression of TGF-β-induced fibrosis in isolated cardiac fibroblasts. mTOR inhibition reversed this effect, indicating that ketone body contributes to cardiac fibroblasts via mTOR pathway. Conclusions These data suggest that ketogenic diet may lead to adverse effects on the remodeling in the hypertensive heart, and they underscore the necessity to fully evaluate its reliability before clinical use.